The impact of natural drivers and human activities on sediment flux in Hekouzhen-Longmen section of China over the last 100 years - Sinuo Fan; Xiaohui Jiang; Yuxin Lei; Xiang Su; Yuehong Li (Journal of Hydrology: Regional Studies)
Study region: Hekouzhen-Longmen Section（the Yellow River middle reaches,China） Study focus: The variations in runoff and sediment in the Yellow River are intricately intertwined with the overall development of the entire river basin. However, there is a conspicuous scarcity of research specifically dedicated to the study of the long-term evolution of the interactions between runoff and sediment. The contribution of vegetation to the reduction of sediment transport was basically calculated inversely based on the contribution of soil and water conservation measures. Additionally, this approach fails to truly reflect the relationship between vegetation in erosion-prone areas and sediment. To fill these research gaps, this study has collated the hydrological and meteorological data over the past century. By applying the method of sediment characteristic factor decomposition, a quantitative analysis has been conducted on the impacts of climate change and human activities on sediment changes. Moreover, by introducing the vegetation coverage in erosion-prone areas, the contributions of soil and water conservation measures implemented during the period of returning farmland to forests to sediment transport have been clarified. This method enables a more accurate understanding of the relative contributions of different factors to the changes in sediment transport, thereby providing a more comprehensive perspective for a thorough understanding of the complex mechanisms of sediment dynamics in the Yellow River. New hydrological insights for the region: Over the past nearly 100 years, the contributions of water yield capacity, sediment concentration, and precipitation to sediment reduction have been quantified as 70.10 %, 34.41 %, and −4.51 % respectively. Notably, the influence of human activities has been on a steadily increasing trajectory over time. During the implementation of the returning farmland to forests, in the areas highly susceptible to erosion, vegetation accounted for 46 % of the reduction in sediment transport, while soil and water conservation measures contributed 54 %. However, considering the waning potential for sediment reduction from the existing soil and water conservation measures, the future management of the Yellow River should place a premium on the rational planning of vegetation and the optimized configuration of engineering measures.